Meningkatkan Produktivitas Karyawan: Pengaruh Kepemimpinan, Budaya Organisasi, dan Kedisiplinan di PLN UP3 Makassar Utara - Fatmala, Fatmala (Fakultas Ekonomi dan Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
The Influence of Leadership Style, Organizational Culture and Discipline on Employee Performance at PT. PLN (Persero) North Makassar Customer Service Implementation Unit.This study aims to determine and analyze the influence of leadership style, organizational culture and discipline on employee performance at PT. PLN (Persero) North Makassar Customer Service Implementation Unit. This type of research is quantitative research using a questionnaire as a source of data collection. This study used 65 respondents using multiple linear regression analysis techniques. The results of this study indicate that: Leadership style has a negative and insignificant effect on employee performance, and Organizational culture has a positive and significant effect on employee performance, discipline has a positive and insignificant effect on employee performance, and then Organizational Culture variable is the most dominant variable influencing employee performance